E-Governance Response in Tackling Covid-19 in Nigeria - Ojo Ann David; Osawe Cyril Onyepuemu; Ibikunle Busayo Qazeem (PERSPEKTIF, 2022)
The outlook of governance in todayâ€™s world is such that any lag in the efficiency, timeliness and responsiveness of public service delivery can result in monumental loss, especially the loss of lives. This was the case with the emergence of corona virus disease (COVID-19) which took world governments, including Nigeria, unawares and necessitated a rapid global effort towards containing the spread of the virus. The notion of ensuring speedy and timely public service delivery was a primary reason for the adoption of e-governance in Nigeria through the digitisation of government processes. Nevertheless, COVID-19 brought human activities to a grinding halt for the most part of the year 2020 as Nigeria, like other nations of the world, implemented a complete shutdown of public and private organisations and placed restrictions on gatherings. With immeasurable deaths and devastations followed by the era of the â€œnew normalâ€ where people were required to reduce possible human contacts, it was certain that e-governance would play a pivotal role in moving forward into the post-COVID-19 era. Adopting the expository research design, the study examines how e-governance could be effective, timely and responsive in addressing and managing the crisis of the COVID-19 pandemic in Nigeria. Analyzing the data from published sources, the study arrived at the realization that e-governance in Nigeria have not been efficient, timely and responsive in handling the pandemic. Some factors that were identified as hindrances to e-governance in tackling the COVID-19 pandemic in Nigeria include lack of public trust in government handling of private data, endemic corruption, high cost of internet services, poor data management system, and so on. Based on the result, the study concludes that e-governance implementation in Nigeria is far from efficient, timely and responsive in addressing pandemics such as COVID-19 and urgent steps must be taken to address the afore-mentioned problems especially as the pandemic continues to linger. It was, therefore, suggested that policymakers be deliberate in establishing a committee that would draft an action plan on COVID-19, set up an e-governance technology development hub, establish a unified national data management system, and develop the political will to combat the virus headlong and record successes in containing the spread of the pandemic.